High-speed aerated jet trajectory simulated by compounding method of Euler-Euler model and meshless SPH method - Junling He; Qingzhi Hou; Jijian Lian; Wenxiao Jia; Panhong Ren (Engineering Applications of Computational Fluid Mechanics)
The flood discharge head is getting higher in high dam construction, threatening the safety of hydraulic engineering. Accurate prediction of the nappe trajectory is needed to help guarantee safety through downstream strategies. However, it is still challenging to accurately obtain the motion trajectory of the aerated jet flow due to dramatic aeration and deformation. This study proposed a compounding method to improve the simulation of high-speed aerated jet flows, combining the advantages of the traditional grid method (jet flow aeration characteristics simulation) and meshless method (broken droplet hydraulic characteristics simulation). The proposed compounding method was verified using test data of a horizontal jet flow with six different initial velocities (ranging from 10 to 20 m/s). The simulated trajectory distances were all in good agreement with the measured data, and the maximum error was less than 3.0% considering air resistance. The air resistance largely influenced the aerated jet trajectory patterns, resulting in a larger flow velocity in the jet centre and a relatively smaller flow velocity at the upper and lower edges. In addition, the thickness of the jet flow increased significantly with increasing initial jet velocity.